ANALISIS INTERNAL CONTROL PENJUALAN PROPERTI PADA PT. CIPUTRA INTERNASIONAL - Palimbong, Desi Diyanti; Karamoy, Herman; Pusung, Rudy J. (JURNAL RISET AKUNTANSI GOING CONCERN, 2017)
Sales is one of the important aspects for the continuity of the company, because of the companys sales earn profit, so the system and control is very important to control the sales activity. The purpose of this research is to analyze the internal control at PT. Ciputra International. Writing method in this research use Descriptive research with data collection method that is interview and observation directly. The results of this study are expected to assist and evaluate the company in the application of sales control procedures. Based on the results of research that the application of control at PT. Ciputra International has complied with generally accepted standards where authorization systems in the sales process become the main guidelines involving marketing, financial, legal, and corporate divisions that are closely interconnected so that the system will react dynamically if there is a change in the sales process. In such cases, the control of the sales process can be controlled effectively and efficiently in accordance with the provisions that become the companys procedure.Keywords: Internal Control and Sales.